Regular and random components in aiming-point trajectory during rifle aiming and shooting - Goodman, S.; Haufler, A.; Shim, J. K.; Hatfield, B. (Journal of Motor Behavior, 2009)
The authors examined the kinematic qualities of the aiming trajectory as related to expertise. In all, 2 phases of the trajectory were discriminated. The first phase was regular approximation to the target accompanied by substantial fluctuations obeying the Weber-Fechner law. During the first phase, shooters did not initiate the triggering despite any random closeness of the aiming point (AP) to the target. In the second phase, beginning at 0.6-0.8 s before the trigger pull, shooters applied a different control strategy: They waited until the following random fluctuation brought the AP closer to the target and then initiated triggering. This strategy is tenable when sensitivity of perception is greater than precision of the motor action, and could be considered a case of stochastic resonance. The strategies that novices and experts used distinguished only in the values of parameters. The authors present an analytical model explaining the main properties of shooting.